Social support, social anxiety, psychological resilience, and antisocial behavior in sports among college students: a cross-sectional study - Chen, Xi; Li, Yi; Zheng, Junkai (Frontiers in Psychology, 2025)
IntroductionThis study explored the relationship between antisocial behavior in sports among college students and social support, as well as the mediating mechanisms of social anxiety and psychological resilience on antisocial behavior in sports.MethodsUsing a simple random sampling survey method, we collected data from 1,421 college students aged 18-24 (female = 604, 42.51%) in Guangzhou and Zhaoqing, China. The Perceived Social Support Scale (PSSS), the Prosocial and Antisocial Behavior in Sport Scale (PABSS), the Liebowitz Social Anxiety Scale (LSAS), and the Connor-Davidson Resilience Scale (CD-RlSC) were utilized.ResultsThe research demonstrates that social support negatively predicts antisocial behaviors in sports (β = −0.108, p < 0.05), with social anxiety serving as a significant mediator (β = −0.096, p < 0.05). Psychological resilience moderates three key relationships: between social support and social anxiety (β = −0.237, p < 0.05); between social anxiety and antisocial behavior (β = 0.173, p < 0.05); and between social support and antisocial behavior(β = −0.198, p < 0.05).DiscussionTo bolster social support, an integrated tripartite supportnetwork (athlete-coach-psychological coach) is recommended. Mechanisms such as structured event retrospectives may enhance psychological resilience, whereas mindfulness training and cognitive restructuring interventions could target social anxiety reduction, thereby potentially attenuating antisocial behaviors.